A theoretical analysis of the relationships shown from the general experimental results of scattering parameters s11 and s21 – exemplified by the film of BaFe12-iCeiO19/polypyrene with i = 0.2, 0.4, 0.6. Issue 3 (31st August 2021) - Liu, Ying; Drew, Michael G. B.; Li, Hexing; Liu, Yue
Abstract: The common practice of applying reflection loss to material is incorrect as it can only be applied to film. Also the dominant theory of impedance matching should be replaced by wave cancellation theory. Here, we show that experimental data obtained from microwave absorption by the film of the titled composite can be successfully analyzed theoretically from our new theories. Formulae for the scattering parameters s 11 and s 21 of the film have been derived based on the wave addition model which clearly differentiates between microwave absorption mechanisms from interface and film. The experimental values, the patterns from s 11 and s 21, and the relationships between the patterns from the experimental values have been reproduced and interpreted both quantitatively and qualitatively from the new perspective. This specific new analysis for the verification of the new theory involving a large data set provides a clear indication that the conclusions obtained are not only valid for one unique system but are of general applicability. Thus, the new theory has been verified and can be used to reveal the mechanisms of microwave absorption by material and device. The successful interpretations are contrasted with the inadequacies of previous applied methods involving reflection loss and impedance matching.